2021
DOI: 10.1111/jdi.13534
|View full text |Cite
|
Sign up to set email alerts
|

CIDEC silencing attenuates diabetic nephropathy via inhibiting apoptosis and promoting autophagy

Abstract: Objective The role of cell death‐inducing DFF45‐like effector C (CIDEC) in insulin resistance has been established, and it is considered to be an important trigger factor for the progression of diabetic nephropathy (DN). We intend to explore whether CIDEC plays an important role in the regulation of DN and its potential mechanism. Methods High‐fat diet and low dose streptozotocin were used to establish type 2 diabetic rat model. We investigate the role of CIDEC in the pathogenesis and process of DN through his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Li et al have reported that cidec plays an important role in lipid metabolism, and abnormal cidec expression can lead to lipid metabolism disorders [ 52 ]. The function of cidec was also reported by foreign scholars, and it was found that cidec expression induced the apoptosis process of cells [ 53 ]. In this study, the expression of cidec and cideb genes was significantly down-regulated, indicating that Streptococcus affected the expression of the cide family in liver tissue, resulting in abnormal liver metabolic function and further liver tissue injury.…”
Section: Discussionmentioning
confidence: 79%
“…Li et al have reported that cidec plays an important role in lipid metabolism, and abnormal cidec expression can lead to lipid metabolism disorders [ 52 ]. The function of cidec was also reported by foreign scholars, and it was found that cidec expression induced the apoptosis process of cells [ 53 ]. In this study, the expression of cidec and cideb genes was significantly down-regulated, indicating that Streptococcus affected the expression of the cide family in liver tissue, resulting in abnormal liver metabolic function and further liver tissue injury.…”
Section: Discussionmentioning
confidence: 79%
“…CIDEC is a key factor in insulin resistance, and its silencing has been linked to the prevention of DN progression [ 31 ]. To determine whether there is an interaction between METTL7A and CIDEC in DN, HG-induced HK-2 cells were transfected with si-METTL7A.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research showed that CIDEC deficiency could mitigate pulmonary vascular remodeling in type 2 diabetes rat models [ 30 ]. A recent study has shown that CIDEC knockdown can ameliorate metabolic abnormalities, insulin resistance, and renal impairment, suppress cell apoptosis and renal fibrosis, and enhance autophagy to prevent DN progression [ 31 ]. Despite little knowledge of the relationship between methyltransferases and CIDEC, evidence has shown that METTL7A also plays a vital role in cell apoptosis and survival [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…High glucose promoted apoptosis and inhibited autophagy of renal tubular epithelial cells with increasing cell death-inducing DFF45-like effector C expression. Inhibiting apoptosis may delay the progression of DN [47] . In addition, the therapeutic effects of zinc supplementation in DN were regulated by increasing hexokinase II expression and the preservation glucose-metabolism-related pathways [48] .…”
Section: Discussionmentioning
confidence: 99%